Assessment of carbon sink capacity and its value accounting for a farmed shellfish in the coastal wetland of the Yalu River Estuary - Hao, Yanju; Tan, Zhenjiang; Cai, Yueyin; Liang, Shengkang; Zhang, Guangshuai; Wang, Quangming; Li, Qing (Frontiers in Aquaculture, 2024)
The carbon sink of cultivation shellfish in coastal wetlands is characterized as both highly ecological and economic value, thus making great contributions to achieving carbon neutrality. In this study, the main species of cultured shellfish (Ruditapes philippinarum, Meretrix meretrix, Sinonovacula constricta, Scapharca suberenata, and Grassostrea gigas) were selected as the research objects in the coastal wetland of the Yalu River Estuary to measure shellfish yields and carbon contents. Combined with the data from the cultured shellfish of fishery statistics of Donggang city, Dandong, Liaoning Province, China, the carbon sequestration capacity was calculated, and the carbon sink values of cultured shellfish also evaluated on the base of the diverse shellfish carbon sequestration ratios. The carbon sink conversion ratio of cultivation shellfish decreased in the following order: S. suberenata, R. philippinarum, G. gigas, S. constricta, and M. meretrix. The total carbon sequestration of cultured shellfish in the Yalu River Estuary Coastal Wetland from 2015 to 2019 was approximately 110,500 tC. The yield and the carbon sequestration quantity of R. philippinarum accounted for 76.60~83.30% of the total yield and 79.07~85.41% of the total carbon sequestration quantity. The value of the carbon sink was approximately 63,710,600 yuan. Among the species of cultured shellfish, R. philippinarum was the largest contributor to the carbon sink value. Based on Tapio’s decoupling model, R. philippinarum has the most ideal state of decoupling between carbon sink and economic growth of cultured shellfish, followed by M. meretrix and S. suberenata. Our results illustrate that the development of coastal wetland shellfish aquaculture has a positive contribution to reducing carbon emissions and increasing carbon sinks.